Crataegus songarica methanolic extract accelerates enzymatic status in kidney and heart tissue damage in albino rats and its in vitro cytotoxic activity. (2nd July 2016) - Ganie, Showkat Ahmad; Ali Dar, Tanveer; Zargar, Sabuhi; Bhat, Aashiq Hussain; Dar, Khalid Bashir; Masood, Akbar; Zargar, Mohammad Afzal
Abstract: Context : Crataegus songarica K. Koch (Rosaceae) has been used in folk medicine to treat various diseases. Objective : This study evaluates the effect of C. songarica methanol extract on the kidney and heart tissue damage of albino rats, and to determine cytotoxic activity of various extracts of songarica on various human cancer cell lines. Materials and methods : Rats were divided into six groups, Group I received water only; Group II received CCl4 (1 mL/kg b wt) intraperitoneal; C. songarica extract (at doses of 100, 200 and 300 mg/kg b wt) orally for 15 days. Cytotoxic activity was determined by SRB method using MCF-7, HeLa, HepG2, SF-295, SW480 and IMR-32 cell lines. Results : Compared with CCl4 group, administration of C. songarica extract at the dose of 300 mg/kg b wt, significantly decreases serum creatinine (59.74%), urea (40.23%) and cholesterol (54 mg/dL), MDA (0.007 nmol/mg protein) in kidney and (0.025 nmol/mg protein) in heart tissue, along with evaluation of GSH (209.79 ± 54.6), GR (111.45 ± 2.84), GPx (94.01 ± 14.80), GST (201.71) in kidney tissue and GSH (51.47 ± 1.47), GR (45.42 ± 6.69), GPx (77.19 ± 10.94), GST (49.89) in heart tissue. In addition, methanol, ethanol and ethyl acetate extracts exhibited potent anticancer activity on six cancer cell lines with IC50 values ranging from 28.57 to 85.106 µg/mL. Discussion and conclusion : Crataegus songarica methanol extract has a potential antioxidant effect as it protects the kidney and heart tissue against CCl4 -induced toxicity, prevents DNA damage and showed strong anticancer activity.